2007
DOI: 10.1162/pres.16.6.655
|View full text |Cite
|
Sign up to set email alerts
|

The Body Surface as a Communication System: The State of the Art after 50 Years

Abstract: The suggestion that the body surface might be used as an additional means of presenting information to human-machine operators has been around in the literature for nearly 50 years. Although recent technological advances have made the possibility of using the body as a receptive surface much more realistic, the fundamental limitations on the human information processing of tactile stimuli presented across the body surface are, however, still largely unknown. This literature review provides an overview of studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 145 publications
0
73
0
Order By: Relevance
“…Regarding stakeholders' issues of lack of tool weight or collision feedback in ergonomics investigations, multi-sensory feedback, combining vision and haptics, is expected to offer performance benefits in tasks in virtual reality (e.g. Swapp et al 2006;Gallace et al, 2007). Multi-sensory feedback is considered essential for some manufacturing tasks (Gomes de Sá and Zachmann., 1999), and is an important aspect of design (Bordegoni et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding stakeholders' issues of lack of tool weight or collision feedback in ergonomics investigations, multi-sensory feedback, combining vision and haptics, is expected to offer performance benefits in tasks in virtual reality (e.g. Swapp et al 2006;Gallace et al, 2007). Multi-sensory feedback is considered essential for some manufacturing tasks (Gomes de Sá and Zachmann., 1999), and is an important aspect of design (Bordegoni et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the fingers are used to stimulate the subject. On the other hand, it has been shown that repeated stimulation of a specific part of the body can lead to an improvement of tactile discrimination performance for that part of the body [41]. This allows the device to meet the user's wishes regarding the location of the HMI in another target body part.…”
Section: Apparatusmentioning
confidence: 99%
“…The communication of actively generated tactile information to the human's skin has been studied for a long time in fields such as virtual reality, accessibility and Sensory Substitution [8]. Researchers utilize artificial haptic stimuli to transmit either abstract information such as warnings, acknowledgements or system states or palpable characteristics of virtual elements such as form or malleability onto the user's skin [8,16].…”
Section: Related Workmentioning
confidence: 99%
“…Researchers utilize artificial haptic stimuli to transmit either abstract information such as warnings, acknowledgements or system states or palpable characteristics of virtual elements such as form or malleability onto the user's skin [8,16].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation